Close - up imaging of Oxia Planum analogue samples under different illumination conditions: preparing for the ExoMars rover mission - Ligeza, Gabriela; Bontognali, Tomaso R. R.; Fayon, Lucile; Bouquety, Axel; Hofmann, Beda; Josset, Jean-Luc; Kuhn, Nikolaus J. (Frontiers in Astronomy and Space Sciences, 2025)
ExoMars is an astrobiology program led by the European Space Agency, which foresees the launch of a rover that will look for signs of past life on Mars. CLUPI, a close-up imager part of the rover’s payload, is designed for capturing high-resolution images of geological samples. Ensuring that each CLUPI image contains a maximum of relevant scientific information is crucial for optimizing the scientific return of the instrument and for the daily tactical planning of the rover’s activities. This study focuses on identifying the preferred lighting conditions for close-up image acquisition in the area that will be explored by the rover: Oxia Planum. To identify lithologies potentially occurring in this region, we conducted a comprehensive review of past publications on Oxia Planum’s mineralogy and geology and analysed image repositories from previous rover missions to guide our selection of samples relevant to the ExoMars mission. These samples were chosen either because we anticipate their presence at the landing site or because they represent highly interesting targets in a mission primarily aimed at finding potential evidence of past microbial life. The samples were categorized into five groups: 1) clastic sedimentary rocks, 2) rocks with Fe-Mg phyllosilicates, 3) igneous rocks, 4) evaporites, carbonates and morphological biosignatures, and 5) rocks with various sedimentary structures. For each group, we identified diagnostic textures visible in CLUPI images. The rocks were photographed using a CLUPI analogue camera under Mars - simulated lighting conditions, varying the proportion of direct and indirect light to mimic morning, evening, and mid-day conditions on Mars, as well as during dust storm conditions. We demonstrated that strategically capturing images at different times of the day under specific illuminations enhances the likelihood of detecting diverse rock textures and relevant structures. Moreover, the images produced in our simulations constitute a reference dataset of Oxia-analogue samples. Thereby, they support the exploration strategy for CLUPI and will help the science team in the decision-making process and data interpretation during the prime mission on Mars.